2018
DOI: 10.1021/acs.chemmater.8b02315
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the Performance of Single-Atom Electrocatalysts: Support-Induced Structural Reconstruction

Abstract: Creating active and stable electrocatalysts remains a highly desirable and critical goal in the fields of catalysis and clean energy conversion. Single-atom catalyst (SAC), as a new research frontier in heterogeneous catalysis, has demonstrated emerging prospects for many electrocatalytic reactions. Supportassisted pyrolysis approaches are widely used in the synthesis of single-atom electrocatalysts. While extensive efforts have been devoted to increase the loading of the atomically dispersed metal sites, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 44 publications
1
31
0
Order By: Relevance
“…The chemical formula demonstrates the overall process of the ORR of the catalyst surface, including the ORR to directly generate H 2 O through an ideal four-electron pathway, or the formation of H 2 O 2 intermediate through an undesirable two-electron pathway. However, the high cost of the traditional Pt catalysts limits large-scale industrial applications [56,116,117]. Lefèvre et al [47] produced microporous carbon-supported iron-based catalysts, whose cathode current density could be comparable to that of platinum.…”
Section: Orrmentioning
confidence: 99%
“…The chemical formula demonstrates the overall process of the ORR of the catalyst surface, including the ORR to directly generate H 2 O through an ideal four-electron pathway, or the formation of H 2 O 2 intermediate through an undesirable two-electron pathway. However, the high cost of the traditional Pt catalysts limits large-scale industrial applications [56,116,117]. Lefèvre et al [47] produced microporous carbon-supported iron-based catalysts, whose cathode current density could be comparable to that of platinum.…”
Section: Orrmentioning
confidence: 99%
“…The above examples indicate that the neighboring atomic environment significantly influences the ORR activity of the isolated metal atoms. In a broader sense, the intrinsic activity of MN x moieties highly depends on the synergy between the single metal atoms and the supports . It was found that the addition of sulfur to the precursor gave an M‐N/C catalyst with enhanced ORR or fuel cell performance, but the mechanisms involved were still controversial .…”
Section: Electrocatalytic Performancementioning
confidence: 99%
“…Reproduced with permission. [82] Copyright 2018, American Chemical Society. Reproduced with permission.…”
Section: Discussionmentioning
confidence: 99%
“…Based on their origins, they can be divided into three types: H 2 O 2 and/or reactive oxygen species (ROS) generated in the reaction, carbon oxidation occurring at high potentials and high temperature, and the instability of low-coordination M-N x sites. [82,[106][107][108] The side effect from H 2 O 2 /ROS on 3dTM-SSCs has been well established. During ORR reaction, aside from the four-electron reduction of oxygen to water, there is a competing twoelectron side reaction that yield H 2 O 2 or ROS as by-products.…”
Section: Challenges For 3dtm-ssc Stabilization At Electrified Interfacesmentioning
confidence: 99%
See 1 more Smart Citation